Investigation of Secondary School Teachers’ Attitudes towards Supporting and Training Courses - Aküzüm, Cemal; Saraçoğlu, Mehtap (Fırat University, 2018)
This research is aimed at revealing the opinions of the teachers working in official state secondary schools relating to the Supporting and Training Courses. The universe of work done using the screening model of quantitative research types, consists of 4081 teachers working in 381 secondary schools in Diyarbakir province in central districts (Bağlar, Kayapınar, Sur, Yenişehir). The sample, according to the study design, consist of 536 teachers selected by means of “criterion sampling” which is one of the purpose sampling methods among the teachers working in secondary schools. The opinions of the teachers about the support and training courses were obtained by using the “Attitude Scale for Supporting and Cultivation Courses” consisting of 3 factors and 22 items developed by the researchers. Data obtained from the study were analyzed via SPSS and AMOS packet programs. The findings of the research show that the attitudes of teachers towards support and training courses are at the highest level, indicating that these courses are in the direction of contributions to both the students and the teachers in the academic direction. On the other hand, it appears that the need to allocate a special time to the courses reflects the lowest level of attitudes towards social life. According to the branch variable, teachers in Turkish, Mathematics, Science, Social Sciences and Foreign Language branches have higher attitudes towards academic contribution of support and training courses than teachers in other branches.

Bu araştırma, resmi devlet ortaokullarında görev yapan öğretmenlerin Destekleme ve Yetiştirme Kurslarına ilişkin görüşlerini ortaya koymaya yönelik bir çalışmadır. Araştırmanın evrenini, Diyarbakır ili merkez ilçelerinde (Bağlar, Kayapınar, Sur, Yenişehir) bulunan 381 ortaokulda görev yapan 4081 öğretmen oluşturmaktadır. Örneklemini ise, araştırmanın desenine uygun olarak, ortaokullarda görev yapan öğretmenler arasından amaçlı örnekleme yöntemlerinden olan “ölçüt örnekleme” yöntemi ile seçilen 536 öğretmen oluşturmaktadır.  Öğretmenlerin destekleme ve yetiştirme kurslarına ilişkin görüşleri, araştırmacılar tarafından geliştirilen 3 faktör ve 22 maddeden oluşan “Destekleme ve Yetiştirme Kurslarına Yönelik Tutum Ölçeği” kullanılarak alınmıştır. Çalışmadan elde edilen veriler SPSS ve AMOS paket programları aracılığı ile analiz edilmiştir. Araştırma bulguları; öğretmenlerin destekleme ve yetiştirme kurslarına yönelik tutumlarının en yüksek düzeyde olduğu boyutun, bu kursların akademik yönden hem öğrencilere hem de öğretmenlere sağladığı katkılar yönünde olduğunu göstermektedir. Buna karşılık, kurslara katılımın özel bir zaman ayırmayı gerektirmesinin ortaya çıkardığı sosyal yaşama olan etkileri boyutunun en düşük düzeydeki tutumları yansıttığı da görülmektedir. Branş değişkenine göre; Türkçe, Matematik, Fen Bilimleri, Sosyal Bilgiler ve Yabancı Dil branşlarındaki öğretmenlerin, Diğer branşındaki öğretmenlere nazaran destekleme ve yetiştirme kurslarının akademik katkısına ilişkin tutumlarının daha yüksek olduğu görülmüştür.
Ortaokul Öğretmenlerinin Destekleme ve Yetiştirme Kurslarına Yönelik Tutumlarının İncelenmesi